Der Aufstieg Chinas und die neuen Kräftekonstellationen in Ostasien - ten Brink, Tobias (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2010)
In the wake of the global slump, China emerged as a major „winner” of worldwide economic and political rebalancing. The paper tries to evaluate the effects of the ascent of China with special regard to current power relations in East Asia. Although China gains in importance and has spearheaded several of the steps toward regional cooperation, there will be no far-reaching political integration under the hegemonic leadership of Beijing in the foreseeable future. In a world marked by economic turbulence, nationalist backlash and American and Japanese challenges to „Sinocentered” Asian regionalism, disintegration tendencies and rivalries will not easily come to an end.